Early-Stage Imaging of Nanocarrier-Enhanced Chemotherapy Response in Living Subjects by Scalable Photoacoustic Microscopy - Nie, Liming; Huang, Peng; Li, Weitao; Yan, Xuefeng; Jin, Albert; Wang, Zhe; Tang, Yuxia; Wang, Shouju; Zhang, Xiaofen; Niu, Gang; Chen, Xiaoyuan (ACS nano, 2014)
Conventional evaluation methods of chemotherapeutic efficacy such as tissue biopsy and anatomical measurement are either invasive with potential complications or dilatory to capture the rapid pathological changes. Here, a sensitive and resolution-scalable photoacoustic microscopy (PAM) with theranostic nanoformulation was developed to noninvasively monitor the therapy response in a timely manner. Ultrasmall graphene oxide nanosheets were designed as both drug-loading vehicle and photoacoustic signal amplifier to the tumor. With the signal enhancement by the injected contrast agents, the subtle microvascular changes of the chemotherapy response in tumor were advantagely revealed by our PAM system, which was much earlier than the morphological measurement by standard imaging techniques. High tumor uptake of the enhanced nanodrug with Cy5.5 labeling was validated by fluorescence imaging. At different observation scales, PAM offered unprecedented sensitivity of optical absorption and high spatial resolution over optical imaging. Our studies demonstrate the PAM system with synergistic theranostic strategy to be a multiplexing platform for tumor diagnosis, drug delivery, and chemotherapy response monitoring at a very early stage and in an effective way.